The experience of the Italian Global Burden of Disease Initiative. (30th September 2020) - Monasta, L
Abstract: In 2007, two groups of Italian researchers started collaborating with the Institute for Health Metrics and Evaluation (IHME) to contribute to the generation of the first GBD 2010 estimates, published in 2012 in The Lancet. Early 2016, the Italian GBD collaborators, 12 at that time, decided to work together, to strengthen the exchange with IHME and gain ownership on the Italian estimates. The group aimed to: 1) exchange experiences, and coordinate activities related to the production and revision of Italian GBD estimates and for specific areas of expertise; 2) disseminate GBD estimates at national and regional level, and foster the active participation of health planners; 3) intensify the sharing of data and information with IHME and reach an agreement for the production of sub-national estimates; and 4) elaborate joint research projects to cover data gaps. In October 2018, IHME agreed to generate sub-national estimates for Italy, which are now being reviewed and will be officially published in May 2021. A thorough analysis of the epidemiological situation in Italy, using GBD 2017, was published in November 2019 in The Lancet Public Health. Other articles are currently being submitted. Researchers are structured in thematic working groups (Core Groups) while Regional Health Authorities are gradually becoming involved, gaining confidence in the use of GBD metrics and contributing to the sub-national revisions. The Italian GBD Initiative held a two-day meeting in Rome in January 2020, to discuss preliminary sub-national estimates. The Core Groups revised the estimates and identified data sources that could further improve the estimates. The results were then discussed with IHME in March 2020. The Italian group can now count on 75 collaborators from 30 research institutes. The Italian bottom-up approach, involving researchers and research institutes without a national political mandate, has shown both positive and negative aspects, as will be discussed during the workshop.